Formulation of hybrid finite-difference time-domain dipole method for lightning induced voltage due to lightning strikes to tall structure - Rameli, Norhidayu (2017)
Lightning cloud delivers a certain amount of charge from the cloud to the earth and may affects power lines either directly or indirectly. In this case of an indirect strike, the coupling between the lightning electromagnetic field and nearby power lines causes a voltage to be induced on the power line. As far as the structure height is concerned, the higher the tower, the greater the chances of it being struck by lightning, which will result in higher induced voltage on the power line compared to the case of a strike to the ground. Consequently, such induced voltage outages and electromagnetic field may cause damage to any equipment exceed as its withstanding capability. Therefore, a proper study needs to be carried out to calculate the lightning electromagnetic field due to the lightning strike to a tall structure in which lightning induced voltages on distribution power line are created due to the lightning electromagnetic field coupling. In this study, the IEEE 1410-2010 guideline was followed to implement the stages of calculating induced voltage, namely, return stroke current, calculating the lightning electromagnetic field and evaluating the interaction of lightning electromagnetic field with the conductor line. For the stages of return stroke current, a model of DU current function as well as the engineering model which based on a distributed source representation were selected. The return stroke current was investigated based on effect of ground reflection factor, in which the effect of soil resistivity and grounding electrode arrangement were included. A new formulation of Hybrid FDTD-Dipole were proposed to calculate the lightning electromagnetic field. This method provide a straightforward formulation which is applicable to any current calculation and able to couple with the line conductor in evaluating the induced voltage. The proposed method was compared with the lightning electromagnetic field measurements at Peissenberg tower, German. Then, the Agrawal model was adopted to evaluate the induced voltage on the power line due to the lightning strike to a tall structure, in which Fukui thermal tower, Japan was used for the validation. The determination of the critical distance between the stricken tall structure and the overhead distribution line at Tanjung Rompin, Pahang, Malaysia was obtained where the results indicated that at least more than 10% reduction of the return stroke current was affected by the changes of ground reflection factor based on the relationship between the soil resistivity and grounding electrode arrangement. Consequently, it also affected the lightning electromagnetic field evaluation, as well as reducing the lightning induced voltage peak by at least 20%. Besides that, the proposed method showed a good agreement with measured values. Lastly, the critical distance obtained showed that the higher the magnitude of lightning current, the longer the distance from a tall tower to the line will be exposed to the induced voltage flashover. Thus, the outcomes of these results may provide very useful information and enhance judgement skills for an electrical power engineer when considering the protection scheme of distribution systems where the lightning induced voltage is the major cause of line outages and affected the overall performance of the system.